React : Zero to Full-Stack (Video Collection) - Wassell, Shaun (Addison-Wesley Professional, 2021)
Web online copy missing! This course contains everything you need to know to become a full-stack developer with the React stack. Prerequisites * Basic knowledge of how programming works * Some experience with the command line (not required) * Ideally, know the basics of HTML, CSS, and JavaScript * At the very least, have a strong grasp of basic programming concepts: variables, arrays, control flow, etc. * Working knowledge of JavaScript * Some experience working on either the front or back end of a web application, but this is not a requirement Description 28+ Hours of Video Instruction React: Zero to Full-Stack video collection is based on four video courses that give you everything you need to become a full-stack developer with the React and MERN stacks. This master class includes the following courses: * Learn JavaScript LiveLessons * Learn React for Modern Web Applications LiveLessons * Node.js Essentials LiveLessons * Full-Stack React LiveLessons Learn JavaScript LiveLessons gives first-time JavaScript users what they need to become successful developers. Shaun Wassell offers a modern, full-fledged introduction to JavaScript. In particular, the viewer learns the modern syntax of JavaScript: ES6. Shaun delivers step-by-step guidance that takes the learner from the basic syntax and concepts of JavaScript, all the way through the more advanced concepts that are covered in technical interviews. Learn React for Modern Web Applications LiveLessons provides a solid foundation in creating modern web applications using the latest version of React. React enables developers to create beautiful, performant, easily maintainable websites incredibly quickly. React is currently the most popular JavaScript framework on the market and is used by a majority of companies, yet it has one of the largest gaps between the number of employers who want it and the number of developers who know it. In short, 33% of employers need React skills, but only 19% of developers say they know React. Node.js Essentials LiveLessons teaches you how to write performant back-end applications in JavaScript by leveraging the Node.js runtime. Several years ago, it wasn't possible to write JavaScript programs for the back end. JavaScript was strictly limited to running in a browser, and if a developer wanted to write back-end software, they had little choice but to learn another programming language, such as PHP. Now, that has all changed. Thanks to Node.js, which enables JavaScript ...